1961
DOI: 10.1126/science.134.3485.1078
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Deuteration of N—CH 3 Group on Potency and Enzymatic N-Demethylation of Morphine

Abstract: Substitution of deuterium for the N-methyl hydrogens of morphine produced a significant reduction in the potency and lethality of morphine in mice regardless of the route of administration. There was no effect on the time of onset, maximal effect, or duration of action. N-demethylation by rat liver microsomal enzymes was characterized by a smaller reaction rate constant, a higher energy of activation, and a larger Michaelis constant with respect to the deuterated morphine. These findings indicated that deutera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
2

Year Published

1962
1962
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 4 publications
1
38
0
2
Order By: Relevance
“…The strength of the radical itself may also play a role. It is possible that the D-PUFA • radical generated from the D 2 -Lin or D 4 -αLnn (similar to pentadien-1,4-yl-3D • ) might be less reactive than the equivalent standard PUFA radical (similar to a pentadien-1,4-yl-3H • ) [56, 57]. This would be the case if the deuterium-containing radical was stabilized relative to hydrogen.…”
Section: Discussionmentioning
confidence: 99%
“…The strength of the radical itself may also play a role. It is possible that the D-PUFA • radical generated from the D 2 -Lin or D 4 -αLnn (similar to pentadien-1,4-yl-3D • ) might be less reactive than the equivalent standard PUFA radical (similar to a pentadien-1,4-yl-3H • ) [56, 57]. This would be the case if the deuterium-containing radical was stabilized relative to hydrogen.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of inhibiting rates of P450 oxidations by C–D substitution has been largely the same since the field of P450 KIE research began (Elison et al, 1961) (which is actually one year before P450s were formally discovered (Omura & Sato, 1962)). KIE measurements have been made in many systems, but what new information has resulted?…”
Section: Examples Of P450 Kie Studiesmentioning
confidence: 99%
“…Thus, the ability to determine the extent to which this step is rate-limiting in a complex cycle is very useful, and therefore many KIE studies have been done. The first report on a P450 KIE appears to be that of Elison et al in 1961 (Elison, Rapoport, Laursen, & Elliott, 1961), who showed that substitution of deuterium in an N -methyl group of morphine slowed its metabolism and increased its potency in rats.…”
Section: Introduction and History Of Cytochrome P450 Kinetic Isotomentioning
confidence: 99%
“…Ellison et ul. (7) studied the pharmacological properties and kinetics of N-demethylation of morphine which has been substituted with deuterium in the N-methyl position. Deuterium substitution effected a slower rate of demethylation and a significant reduction in pharmacologic potency.…”
mentioning
confidence: 99%